Participation in everyday activities and quality of life in pre-teenage children living with cerebral palsy in South West Ireland - Corcoran Paul; Mc Manus Vicki; Perry Ivan J (BMC, 2008)
Abstract Background Cerebral palsy (CP) is the most common cause of physical disability in children but its impact on quality of life is not well understood. This study examined participation in everyday activities among children without CP and children with mild, moderate and severe impairment due to CP. We then examined ten domains of quality of life in children with CP and investigated whether participation in everyday activities was associated with improved quality of life independent of gender, age and level of impairment. Methods This was a cross-sectional study of children aged 8-12 years based on two questionnaires, frequency of participation (FPQ) and KIDSCREEN, completed by parents of 98 children on the South of Ireland Cerebral Palsy Register (response rate = 82%) and parents of 448 children attending two Cork city schools (response rate = 69%) who completed one questionnaire (FPQ). Multiple linear regression was used: firstly to estimate the effect of severity of CP on participation in everyday activities independent of age and gender and secondly we estimated the effect of participation on quality of life independent of age gender and level of impairment. Results Participation in 11 of the 14 everyday activities examined varied across the children without CP and the children with varying severity of CP. In general, increased impairment decreased participation. Independent of age and gender, there was a highly significant decrease in overall participation with a fall of -6.0 (95% CI = -6.9 to -5.2) with each increasing level of impairment. The children with CP generally had high quality of life. Increased impairment was associated with diminished quality of life in just two domains - Physical well-being and Social support and peers. Overall participation in everyday activities was significantly associated with quality of life in 3 of the 10 domains (Physical well-being, Social support and peers & Moods and emotions) in analysis adjusted for gender age and level of impairment. Conclusion While increased impairment due to CP restricts participation in the majority of everyday activities, the level of participation has a limited effect on the quality of life of the children with CP in age 8-12 years.